1988
DOI: 10.1111/j.1365-2818.1988.tb01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Tip‐bias induced surface modification on gold surfaces

Abstract: We have observed drastic modification of gold surfaces at tip biases above a threshold value. These modifications were observed only on surfaces which are not atomically flat and only with negative tip bias. We tentatively attribute these surface modifications to formation of Taylor cones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…1979, 83, 114. (17) Pilling, M. J., Smith, I. W. M., Eds. Modern Gas Kinetics•, Blackwell: Oxford, U.K.. 1987; p 99. entropy change (1 atm standard state), /?…”
Section: Discussionmentioning
confidence: 99%
“…1979, 83, 114. (17) Pilling, M. J., Smith, I. W. M., Eds. Modern Gas Kinetics•, Blackwell: Oxford, U.K.. 1987; p 99. entropy change (1 atm standard state), /?…”
Section: Discussionmentioning
confidence: 99%
“…Au surfaces after operation at high current and/or bias to melting [54,55]. Nagahara et a1 reported that increasing the tip bias beyond -1.4 V caused rough areas on a Au sample to blister and become unstable [54]. They were unable to cause the same effect on smooth gold surfaces for biases as large as 2.5 V. Platinum (which has a higher melting point) did not exhibit blistering on either rough or smooth surfaces.…”
Section: Several Groups Have Attributed Changes Observed Onmentioning
confidence: 99%
“…Au surfaces after operation at high current and/or bias to melting [54,55]. Nagahara et a1 reported that increasing the tip bias beyond -1.4 V caused rough areas on a Au sample to blister and become unstable [54].…”
Section: Several Groups Have Attributed Changes Observed Onmentioning
confidence: 99%
“…single crystals. 6 They conclude that contamination probably plays an important role in this effect. The authors also state the existence of a minimum threshold for negative biases (no numbers given) but found no effect at all for positive biases.…”
Section: Introduction Consequences 01f Bias Voltagementioning
confidence: 97%